An agent-based model to explore urban policies, pedestrian behaviour and walkability. (2018) - Tsaples, Georgios; Fancello, Giovanna
The purpose of this paper is to use the agent-based methodology both as a research tool to study pedestrian behaviour and as a decision support system for urban authorities aimed to improve walkability. The developed model represents an urban environment with its citizens/agents performing movements under different means of transport and towards different destinations. Different scenarios, demonstrated that by improving the conditions of the urban environment people walk more and a bigger part of the environment is considered as 'favourite for walking'. Moreover, the conduciveness to walk affects the daily peoples' behaviour, and acts also as a positive influence to economic activity.